Catheter‐related bloodstream infection caused by Enterococcus spp. (22nd May 2012) - Reigadas, E.; Rodríguez‐Créixems, M.; Guembe, M.; Sánchez‐Carrillo, C.; Martín‐Rabadán, P.; Bouza, E.
Abstract The role of Enterococcus spp. as a cause of catheter‐related bloodstream infections (CR‐BSI) is almost unexplored. We assessed the incidence and clinical characteristics of enterococcal CR‐BSI (ECR‐BSI) over an 8‐year period in our hospital. We performed a retrospective study (January 2003 to December 2010) in a large teaching institution. We recorded the incidence, and the microbiological and clinical data from patients with ECR‐BSI. The incidence per 10 000 admissions for enterococcal BSI and ECR‐BSI was 25 and 1.7, respectively. ECR‐BSI was the fourth leading cause of CR‐BSI in our institution (6%). A total of 75 episodes of ECR‐BSI were detected in 73 patients (6% of all enterococcal BSI). The incidence of ECR‐BSI increased by 17% annually (95% CI 19.0–21.0%) during the study period. Nineteen percent of ECR‐BSI episodes were polymicrobial. Overall mortality was 33%. ECR‐BSI is an emerging and increasingly common entity with a high mortality. This finding should be taken into account when selecting empirical treatment for presumptive CR‐BSI.